PENGARUH ETIKA DAN SISTEM PENGENDALIAN MUTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN DENGAN SKEPTISME PROFESIONAL SEBAGAI VARIABEL MODERASI - Anisa Septiana Dewi; Amalia Fakhrunnisa (Prosiding Seminar Nasional Pakar, 2020)
This research aims at examining the impact of ethics and quality control systems on the ability of auditors to detect fraud and that professional skepticism moderate the effect of ethics and quality control systems with respect to the ability of auditors to detect fraud. The theory of attribution used as theoritical studies in this research. The sample in this study as many as 79 people were selected using a purposive sampling technique. Multiple linear regression analysis used in this study as data analysis techniques. Before doing the regression analysis conducted testing research instrument and test the assumptions of classical regression analysis results for accuracy. Based on the results, it showed thatthe ethics has a negative effect on the ability of auditors to detect fraud, while the quality control systems in the opposite way. It has also been found that professional skepticism do not undermine the influence of ethics with respect to the ability of auditors to detect fraud. Furthermore, it does not strengthen the influence of quality control systems on the ability of auditors to detect fraud.